SEED BANK GULMA PADA BERBAGAI POLA TANAM DAN BERBAGAI KEDALAMAN DI LAHAN PASIR - Rahayu Widowati; Endah Ratnaningsih (JURNAL VIGOR, 2021)
The research was about seed bank of weed on cropping pattern various and soil depth in coastal sandy land conducted to know density, compostion and diversity of weed on three lands weed different of soil depth and cropping patent. The research with the sampling of soil object in Bugel Beach, Panjatan District, Kulonprogo Regency, Special Province of Yogyakarta. The Palace to grow of seed bank in green house on Agriculture Departement, Faculty of Agriculture, Gadjah Mada University, Yogyakarta. The experimental design was Randomized Complete Block Design (RCBD) Factorial with two factors and three replications. The first factor was kinds of cropping pattern consisted of “bero”, cropping pattern in rotation and cropping pattern of intercropping. The second factors was soils depth consisted of 0-5 cm, 5-10 cm, 10-15 cm and 15-30 cm. The result showed that high density level be obtained on intercropping lands on 5-10 cm soils depth. The composition from seed bank be obtained broadleaf weeds was dominated in all of lands, the dominate of broadleaf were Oldenladia corymbosa, herbaceous of Eragrostis tenela, Digitaria sanguinalis and Cyperis compresus, C. rotundus. The diversity from seed bank on three of lands from four of soils depth was the weed isn’t homogene. Key word: seed bank, cropping pattern, soil depth, snady land